HF and CKD present a dire prognosis in young Type 2 Diabetic patients. (14th October 2021) - Seabra Carvalho, D; Gavina, C; Valente, F; Bernardo, F; Santos Araujo, C; Taveira Gomes, T
Abstract: Introduction: Type-2 diabetes (T2D) is one of the most relevant risk factors for both heart failure (HF) and chronic kidney disease (CKD). Target organ damage causes significant morbi-mortality, especially when these two conditions are combined with diabetes. Understanding the natural history of the combination of these conditions is paramount to implement tailored preventive measures. Purpose: To estimate the risk of all-cause death, cardiovascular (CV) death and non-fatal major CV events (MACE) in T2D patients younger than 65 years, either: i) without HF or CKD, ii) with HF (T2D-HF), or iii) with CKD (T2D-CKD) in a real-world clinical setting. Methods: Retrospective cohort study performed in a healthcare centre that provides primary and secondary care. It included adults with T2D aged between 40 and 65 years of age stratified into three groups: i) T2D with HF defined as either: Ejection Fraction (EF) ≤40% and NT-proBNP ≥200pg/mL (≥600pg/mL if atrial fibrillation (AF)) or BNP ≥100pg/mL (≥125pg/mL if AF); EF >40% in the presence of structural cardiac abnormalities), ii) T2D with CKD (eGFR ≤60mL/min using EPI-CKD formula) and T2D without HF or CKD. We modelled 1-year risk for CV death, all-cause mortality and non-fatal MACE using multivariate weighted cox regression models clustered by patient. Models were adjusted for age (using penalized splines), sex, age-sex interaction, prior history of hypertension, myocardial infarction, stroke, and peripheral arterial disease. We reported hazard ratios (versus T2D without HF or CKD) with 95% confidence intervals. Results: We identified 14986 patients with T2D without HF or CKD, 1101 with T2D with HF and 3114 with T2D with CKD. Patients were in general 55–58 years old, with a slight predominance of the male gender across the groups. Event rate was 14% in T2D with HF, 15% in T2D with CKD and 5% in TD2 without these conditions. One-year all-cause death risk was 2.77 (2.26–3.40) for T2D-HF and 3.09 (2.77–3.45) for T2D-CKD. CV death risk was 2.59 (1.72–3.91) for T2D-HF and 2.75 (2.19–3.46) for T2D-CKD. Non-fatal MACE risk was 2.82 (2.34–3.41) for T2D-HF and 1.90 (1.66–2.17) for T2D-CKD. Regarding MACE, the event rate was 32% in T2D-HF, 13% in T2D-CKD but only 6% in T2D. T2D-HF was associated with the highest risks of myocardial infarction (3.25 [2.60–4.06]) and end-stage kidney disease (9.9 [7.3–13.43]) when compared to T2D-CKD. Conclusions: Young patients with T2D combined with HF or CKD have an increased risk of early adverse CV and renal events. HF was linked with highest risk of myocardial infarction and end-stage kidney disease. These findings highlight the importance of an early identification and management of HF and CKD in T2D patients. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AstraZeneca Produtos Farmacêuticos Lda